The Depiction of Chicago Gangster Era in American Filmography - Kopp, Lukáš (Univerzita Pardubice, 2021)
This thesis discusses the depiction of Chicago gangster era in the selected filmography. First, the paper provides the theoretical background by describing the history of the city and the social problems associated with the changes Chicago experienced at the start of the 20th century. This part also discusses movie history and gangster characters. Secondly, the analysis of the selected movies is divided into three chapters discussing different aspects of the films. At the end, a conclusion on how the movies reflect the real situation in the city and what is the tendency of the film makers towards the depiction of gangsters is made.
Obraz Chicagské gangsterské éry v americké filmografii
Keywords: Chicago; gangsteři; sociologie; filmy; historie; Chicago; gangsters; sociology; movies; history